Impact of family support on chemotherapy adherence among breast cancer patients: A Cross-Sectional Study in Indonesia - Muhammad Farhan Syahrefi; Upik Pebriyani; Muhammad Hatta; Asri Mutiara Putri (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2025)
Introduction: Breast cancer remains the most prevalent malignancy among Indonesian women, comprising approximately 30% of all cases. Most patients present in advanced stages, necessitating chemotherapy, which often causes side effects such as alopecia, nausea, and anxiety that may reduce treatment adherence. Family support plays a vital psychosocial role in enhancing motivation and compliance. Methods: This observational analytical study employed a cross-sectional design at Dr. H. Abdul Moeloek Regional General Hospital, Bandar Lampung, from June 20 to 30, 2025. A total of 47 breast cancer patients undergoing chemotherapy were selected through purposive sampling. Family support was assessed via a validated questionnaire, and adherence data were extracted from medical records. The Chi-square test was applied with a significance level of α = 0.05. Results: Most respondents were aged 46–60 (44.7%) and worked as housewives (55.3%). Good family support was reported by 68.1% of participants, and 72.3% demonstrated good chemotherapy adherence. Statistical analysis revealed a significant association between family support and chemotherapy adherence (p = 0.000 < 0.05). Patients with strong family support consistently showed higher adherence levels. Conclusion: Family support has a significant influence on chemotherapy adherence in breast cancer patients. Interventions that strengthen family involvement could enhance treatment success and improve patient quality of life. Integrating psychosocial support into cancer care programs is crucial for addressing both medical and emotional needs, thereby promoting optimal adherence and therapeutic outcomes.